Histo Hepatic Alterations in Commercially Important Fish (Pseudoplatystoma corruscans Spix & Agassiz, 1829) Exposed to a Glyphosate-Based Herbicide - Ribeiro, Aline Aparecida; Trindade, Wesley Alves; Favetta, Paula Montanhini; Geronimo, Edson; Iukava, Lidia Kazue; Benedito, Evanilde; Germano, Ricardo de Melo (Journal of Agricultural Studies, 2021)
The presence of herbicides in the aquatic environment can cause different effects at all levels of biological organization. This study aimed to evaluate the hepatic alterations of the herbicide Roundup WG® on juvenile Pseudoplatystoma corruscans exposed to three different concentrations of this chemical compound: 0.25g/1000L, 0.50g/1000L, and 0.75g/1000L, plus control treatment (0.00g/1000L). The experiment lasted sixty days and, in the end, liver fragments were collected for further histological processing, using the hematoxylin-eosin (HE) technique. Only the control group showed a statistically significant increase in body mass and total length during the experiment. Blood glucose also showed no difference among the sample groups. The lesions found in the liver considered severe were hemorrhage, vacuolization, and hypertrophy of hepatocytes and the presence of free melanomacrophages, recorded in the groups exposed to 0.50 and 0.75g/1000L. The results obtained in the present study indicate that the herbicide Roundup WG® can promote liver alterations in Pseudoplatystoma corruscans.